Preparedness and response to an emerging health threat—Lessons learned from Candida auris outbreaks in the United States. (9th November 2021) - Meyer, Diane; Martin, Elena K.; Madad, Syra; Dhagat, Priya; Nuzzo, Jennifer B.
Abstract: Objective: Candida auris infections continue to occur across the United States and abroad, and healthcare facilities that care for vulnerable populations must improve their readiness to respond to this emerging organism. We aimed to identify and better understand challenges faced and lessons learned by those healthcare facilities who have experienced C. auris cases and outbreaks to better prepare those who have yet to experience or respond to this pathogen. Design: Semi-structured qualitative interviews. Setting: Health departments, long-term care facilities, acute-care hospitals, and healthcare organizations in New York, Illinois, and California. Participants: Infectious disease physicians and nurses, clinical and environmental services, hospital leadership, hospital epidemiology, infection preventionists, emergency management, and laboratory scientists who had experiences either preparing for or responding to C. auris cases or outbreaks. Methods: In total, 25 interviews were conducted with 84 participants. Interviews were coded using NVivo qualitative coding software by 2 separate researchers. Emergent themes were then iteratively discussed among the research team. Results: Key themes included surveillance and laboratory capacity, inter- and intrafacility communication, infection prevention and control, environmental cleaning and disinfection, clinical management of cases, and media concerns and stigma. Conclusions: Many of the operational challenges noted in this research are not unique to C. auris, and the ways in which we address future outbreaks should be informed by previous experiences and lessons learned, including the recent outbreaks of C. auris in the United States.